An ILS algorithm with RVND for the green vehicle routing problems with time-varying speeds - Mendes Júnior, Darci José; Gonçalves, Luciana Brugiolo; Soares, Stênio Sã R. F. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2018.4452, 2018)
The environmental impacts of human action have led several countries to create stricter laws and tax breaks to reduce this damage. Thereby, the Green Logistic has been increasingly sought to meet the requirements and needs for a more sustainable development. This work presents an ILS (Iterated Local Search) algorithm combined with RVND (Random Variable Neighborhood Search) and compare it with a GRASP (Greed Randomized Search Procedure) algorithm where each one has two variations: minimize distance and minimize emission. The results show the effectiveness of the ILS approach and heuristics that minimize the total distance covered do not present themselves as good solutions in terms of sustainability.